Assessment of the Quality of Newly Formed Bone around Titanium Alloy Implants by Using X-Ray Photoelectron Spectroscopy - Hiroshi Nakada; Toshiro Sakae; Yasuhiro Tanimoto; Mari Teranishi; Takao Kato; Takehiro Watanabe; Hiroyuki Saeki; Yasuhiko Kawai; Racquel Z. LeGeros (International Journal of Biomaterials)
The aim of this study was to evaluate differences in bones quality between newly formed bone and cortical bone formed around titanium alloy implants by using X-ray photoelectron spectroscopy. As a result of narrow scan measurement at 4 weeks, the newly formed bone of C1s, P2p, O1s, and Ca2p were observed at a different peak range and strength compared with a cortical bone. At 8 weeks, the peak range and strength of newly formed bone were similar to those of cortical bone at C1s, P2p, and Ca2p, but not O1s. The results from this analysis indicate that the peaks and quantities of each element of newly formed bone were similar to those of cortical bone at 8 weeks, suggestive of a strong physicochemical resemblance.